Numerical and analytical prediction of pressure and impulse from vented gas explosion in large cylindrical tanks - Li, Jingde; Hao, Hong (ELSEVIER SCIENCE BV, 2019)
© 2019 Institution of Chemical Engineers This paper presents an extension of previous study on estimating the internal and external pressure and impulse from vented gas explosion in large cylindrical tanks. Unlike the small-medium scale explosion from cylindrical tanks in previous work, explosion pressure and impulse from large-scale explosions are numerically and analytical investigated in this study. CFD simulations are conducted and validated by using experimental data. Sensitivity study on grid selection for large-scale explosion simulations is performed. By adopting two scale-up factors for the analytical correlations, the internal pressure and external pressure on adjacent tanks from vented gas explosion in a tank are accurately predicted. Parametric study of the effectiveness of separation gap between adjacent tanks on pressure and impulse mitigation is also carried out. Influences of the venting size, tank diameter and tank height on the effectiveness of separation distance for pressure and impulse mitigation from large-scale vented gas explosion in an adjacent tank are studied.